The Prevalence and Awareness of Regular Follow Up of Patients Treated with Phototherapy for Skin Cancer Surveillance - Alsuwaidan S; AlNasser SN; Almuhaideb QA; Nouri MT; Aldossari AA; Alsuhibani AS; Alajlan A (Dove Medical Press, 2024)
Sami Alsuwaidan,1 Sultan Nasser AlNasser,2 Qais Adel Almuhaideb,3 Mohammad Talal Nouri,4 Abdulelah Abdulhadi Aldossari,2 Alanoud Sultan Alsuhibani,5 Abdulmajeed Alajlan1 1Department of Dermatology, College of Medicine, King Saud University, Riyadh, Saudi Arabia; 2College of Medicine, King Saud University, Riyadh, Saudi Arabia; 3Department of Dermatology, King Faisal Specialist Hospital & Research Centre, Riyadh, Saudi Arabia; 4Department of Plastic Surgery, King Abdulaziz Medical City, Ministry of National Guard - Health Affairs (MNGHA), Riyadh, Saudi Arabia; 5College of Medicine, King Saud bin Abdulaziz University for Health Sciences, Riyadh, Saudi ArabiaCorrespondence: Sultan Nasser AlNasser, College of Medicine, King Saud University, Riyadh, Saudi Arabia, Tel +966556974586, Email SultanAlNasser70@gmail.comObjective (Background): Regular full-body skin examination is commonly ignored in patients post-phototherapy, despite ultraviolet (UV) radiation being carcinogenic. Our objectives are to assess the prevalence of regular follow-up and full-body skin examination for patients treated with phototherapy, as well as the relationship between phototherapy exposure and the development of skin cancer in Saudi Arabia.Methods (Settings, Design): This was a cross-sectional retrospective study conducted from January 2022 to July 2022. The study included 99 patients, selected via simple random sampling, from King Saud University Medical City, Riyadh, Saudi Arabia, who underwent phototherapy for at least 8 weeks and were followed for a minimum of 18 months post-treatment. Patients who met the inclusion criteria were called and given a questionnaire.Results: Out of 99 patients, only 26 (26.26%) underwent full-body skin examinations by their physicians after phototherapy treatment. The average follow-up time after phototherapy was 3.2 years. Most study participants (85.85%) were unaware that cancer was a possible complication of phototherapy. Participants with knowledge about skin cancer complications were more likely to have undergone a full-body exam (P = 0.001). None of the participants developed any type of skin cancer after phototherapy.Conclusion: Patients treated with phototherapy had no adequate information about the risk of skin cancer. The incidence of skin cancer was zero in our small cohort. Dermatologists in Saudi Arabia do not have an evidence-based notion regarding the risk of skin cancer among the Arab population after phototherapy. Since There is a lack of data examining the relationship between phototherapy and skin cancer in the Arab region, this study should trigger future studies with large populations and longer follow up periods.Keywords: phototherapy, skin cancer, skin examination